2018
DOI: 10.5796/electrochemistry.17-00089
|View full text |Cite
|
Sign up to set email alerts
|

A New Prospect for Stabilization of Graphite Electrode/Electrolyte Interface in Bis(fluorosulfonyl)imide Anion-based Ionic Liquid Electrolyte

Abstract: We investigated effects of high lithium bis(fluorosulfonyl)imide (LiFSI) salt concentration or heat treatment before initial charge on charge-discharge performance of a graphite electrode in a 1-ethyl-3-methylimidazolium (EMImFSI)-based ionic liquid (IL) electrolyte. LiF was observed at the surface of graphite electrodes taken out from 2.00 mol kg −1 LiFSI/EMImFSI system and from 0.32 mol kg −1 LiFSI/EMImFSI system with pre-heat treatment before the initial charge. The surface LiF effectively suppresses the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…It has been calculated that the reduction potential of LiFSI could be as high as 2.3 V for the concentrated LiFSI/DME electrolyte in lithium sulfur batteries, though a high thermal energy is needed to initiate the reduction [44] . A similar observation was reported by Uchida et al [45] . with the use of the LiFSI/EMIm.FSI ionic liquid electrolyte, where LiF on the surface of graphite was observed, indicating the reduction of FSI − anion.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…It has been calculated that the reduction potential of LiFSI could be as high as 2.3 V for the concentrated LiFSI/DME electrolyte in lithium sulfur batteries, though a high thermal energy is needed to initiate the reduction [44] . A similar observation was reported by Uchida et al [45] . with the use of the LiFSI/EMIm.FSI ionic liquid electrolyte, where LiF on the surface of graphite was observed, indicating the reduction of FSI − anion.…”
Section: Resultssupporting
confidence: 64%
“…with the use of the LiFSI/EMIm.FSI ionic liquid electrolyte, where LiF on the surface of graphite was observed, indicating the reduction of FSI − anion. It is reported that a high temperature pretreatment is needed (or cycling at elevated temperatures) for the relatively low concentration LiFSI/EMIm.FSI (0.32 m ) electrolyte to form a LiF rich SEI layer on the graphite through a non‐electrochemical mechanism [45] . Recently, Alvarado et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, he moved to AIST as a researcher. Uchida has been extensively engaged in research on lithium secondary batteries focusing on positive electrode materials, [185][186][187] composite electrode design, 188,189 and electrode/electrolyte interfaces, 190,191 one of which has received the Excellent Paper Award of ECSJ in 2018. 186 In recent years, he has also focused on elucidating ion transport phenomena in non-aqueous electrolytes and has published several papers on this subject.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…[26][27][28] In the IL electrolytes used in the present study, the SEI layer is believed to be generated by the decomposition of FSA and TFSA anions. 14,16,[29][30][31][32][33] Fig. 5 1 eV), which is known as one of the SEI components having high Li-ion conductivity.…”
Section: Materials Advances Papermentioning
confidence: 99%